Streptozotocin, 1982-2022: Forty Years from the FDA's Approval to Treat Pancreatic Neuroendocrine Tumors - Capdevila, Jaume; Ducreux, Michel; García Carbonero, Rocio; Grande, Enrique; Halfdanarson, Thorvardur; Pavel, Marianne Ellen; Tafuto, Salvatore; Welin, Staffan; Valentí, Vicente; Salazar, Ramón (Neuroendocrinology, 2022)
In May 1982, the US Food and Drug Administration (FDA) approved the use of streptozotocin to treat pancreatic neuroendocrine tumors (panNETs). Thus, this year marks 40 years since that landmark date. This review of streptozotocin to treat panNETs is intended to commemorate this anniversary. A historical perspective of the chemical structure, pharmacokinetics, and mechanism of action of streptozotocin is followed by data from prospective and retrospective clinical studies. The last section of the review addresses the latest aspects and takes note of the prospects that lie ahead on the future horizon of the use of streptozotocin to treat panNETs, including ongoing clinical trials.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Historical review; Pancreatic neuroendocrine tumors; Streptozotocin